An Explorative Survey in the Implementation of Good SMES Governance on Small Business Entity - Syam BZ, Fazli (Journal of Accounting Research, Organization and Economics, 2018)
Objective This study aims to explain and predict about the implementation of good governance on small business entities as a key performance indicator. Implementation of good governance is needed and becomes important for small business entities to be able to develop and still exist in business environments.Design/methodology This study was designed with field study research approach oriented explorative study with a combination of primary and secondary data. This research proposed two precision, namely: First, an understanding of small business entities on the principles of SMEs governance is positively associated with perceptions of small business entities about the importance of implementing good governance in business activities. Second, the perception on the implementation of good governance is positively associated with the performance of small business entities.Results The results showed that the understanding of small business entities are positively related to perceptions of the importance of implementing good governance, but not positively related to the performance of small business entities. This means that the constraints and obstacles faced by small business entities in the application and implementation of good governance is more due to the principles of SMEs governance do not have a positive and significant relationship with the performance of small business entities.Research limitations/implications For further research is needed to add more small business entities as respondents, particularly small business entity that has the legality (listed in the government and/or have a business license.) Necessary to reexamine the instrument that has been used to make some adjustments such as set back a list of questions compiled by Credit Lyonnais Securities Asia (CLSA) to make some adjustments in accordance with the needs of small business entities. Further research is recommended to use the same method or using other research methods in the test results, such as using Discriminate Analysis.Keywords Good SMEs Governance, Key Performance Indicators, CG Indicators, Small Business Entity